Immunogenicity of embryonic stem cell-derived progenitors after transplantation. - English, K; Wood, K (2011)
PURPOSE OF REVIEW: This review focuses on the immunogenicity of embryonic stem cell (ESC)-derived progenitors and the impact of the immune response on applications of cell replacement therapy (CRT). Possible strategies to induce immunological tolerance to ESC-derived progenitor cells will also be discussed. RECENT FINDINGS: Evidence for the differential epigenetic control of major histocompatibility (MHC) and antigen processing molecules in ESCs and differentiated ESCs has recently been described. The presence of T cells recognizing the pluripotency-associated transcription factor octamer-binding transcription factor 4 (OCT4) in healthy patient-derived peripheral blood mononuclear cells adds further complexity to the immune response against ESCs and ESC-derived progenitors. SUMMARY: Although ESCs and ESC-derived progenitors appear to exert some level of immune privilege in specific circumstances, these allogeneic cells are indeed recognized by the immune system and can be subject to mechanisms of rejection. Herein, we discuss the importance of the recent reports describing an immunosuppressive capacity of ESCs, and the epigenetic control of MHC in ESCs and how these characteristics may be harnessed in the development of strategies to induce immunological tolerance.